Feather mites of the subfamily Proctophyllodinae (Acari: Proctophyllodidae) from passerines (Aves: Passeriformes) in Costa Rica - Mironov, Sergey V.; Literak, Ivan; Sychra, Oldrich; Capek, Miroslav (Zootaxa, 2017)
The paper provides new data on systematics and host associations of feather mites of the subfamily Proctophyllodinae (Astigmata: Proctophyllodidae) recorded on passerine birds (Passeriformes) in Costa Rica. A total of 25 proctophyllodine species of six genera have been recorded, of which 19 new species are described: Anisophyllodes cuneiformis sp. n. from Sittasomus griseicapillus (Vieillot) (Furnariidae), Atrichophyllodes latilobus sp. n. from Hylophylax naevioides (Lafresnaye) (Thamnophilidae), Nycteridocaulus attila sp. n. from Attila spadiceus (Gmelin, JF) (Tyrannidae), N. hylophylax sp. n. from Hylophylax naevioides (Lafresnaye) (Thamnophilidae), N. ketourus sp. n. from Thryophilus rufalbus (Lafresnaye) (Troglodytidae), N. leptopogoni sp. n. from Leptopogon superciliaris Tschudi (Tyrannidae), N. myiobius sp. n. from Myiobius sulphureipygius (Sclater, PL) (Tyrannidae), N. myioborus sp. n. from Myioborus miniatus (Swainson) (Parulidae), N. platyrinchi sp. n. from Platyrinchus cancrominus Sclater, PL and Salvin (Tyrannidae), Platyacarus caulifer sp. n. from Glyphorynchus spirurus (Vieillot) (Furnariidae), Pl. dendrocinclae sp. n. from Dendrocincla homochroa (Scalter, PL) (Furnariidae), Pl. dendrocolapti sp. n. and Pl. picumnus sp. n. from Dendrocolaptes picumnus Lichtenstein, MHK (Furnariidae), Pl. sclerurus sp. n. from Sclerurus mexicanus Sclater, PL (Furnariidae), Proctophyllodes arremoni sp. n. from Arremon brunneinucha (Lafresnaye) (Emberizidae), Pr. euphoniae sp. n. from Euphonia hirundinacea Bonaparte (Fringillidae), Pr. vesicularis sp. n. from E. anneae Cassin (Fringillidae), Pr. parkesiae sp. n. from Parkesia motacilla (Vieillot) (Parulidae), and Pr. strictophyllus sp. n. from Coereba flaveola (Linnaeus) (Thraupidae). The female of Anisophyllodes pipromorphae Atyeo, 1967, previously known from two forms of males only, is described for the first time.        Five new host associations are recorded for the following mites: Anisophyllodes pipromorphae from Mionectes olivaceus Lawrence (Tyrannidae), Diproctophyllodes dielytra (Trouessart, 1885) from Chiroxiphia linearis (Bonaparte) and Corapipo altera Hellmayr (Pipridae), Nycteridocaulus pectinatus Atyeo, 1966 from Tolmomyias sulphurescens (von Spix) (Tyrannidae), and Proctophyllodes thraupis Atyeo and Braasch, 1966 from Tangara icterocephala (Bonaparte) (Thraupidae).        Two species, Proctophyllodes habiae Atyeo and Braasch, 1966 from Habia rubica (Vieillot) (Cardinalidae) and Platyacarus sittasomi Hernandes et al., 2007 from Sittasomus griseicapillus (Vieillot) (Furnariidae), are recorded in Costa Rica for the first time.        New diagnoses and keys to all currently known species are provided for the genera Anisophyllodes Atyeo, 1967, Atrichophyllodes Hernandes et al., 2007, Nycteridocaulus Atyeo, 1966, and Platyacarus Kudon, 1982. Two new species groups, caulifer and minor, are established within the genus Platyacarus. The history of taxonomic investigations of proctophyllodine feather mites is briefly presented. We summarize host associations with passerine birds of the New World for these proctophyllodine genera and species, excluding the genus Proctophyllodes.